PENDAMPINGAN DALAM STRATEGI PEMASARAN PADA UMKM DI DESA KUALA SEMPANG - Risnawati, Risnawati; Ginola Tri Shindy; Anggia Sekar Putri; Octaviani, Octaviani; Nanda Putri; Novitri Rahmawati; Salsabila, Salsabila; Risa Febriyatna (Bajang Institute, 2025)
Marketing strategy is a measurable action intended to introduce company products to the wider community. A marketing strategy is a collection of business steps that have been combined at the level of product introduction to making consumers make purchases. The problem we encountered was related to marketing strategies that had not been implemented properly in Kuala Sempang Village. For this reason, we held